Construction of new exact solutions of the resonant fractional NLS equation with the extended Fan sub-equation method - Kalim U. Tariq (Elsevier, 2021)
The fucus of this study is to find a set of some novel solutions concerning the resonant fractional nonlinear Schrödinger equation (R-FNLSE) with quadratic-cubic nonlinearity by employing the extended FAN sub-equation approach. The parameter α∈(0,1] is the core constraint which simulate the flow rate propagation, plays a key rote in telecommunications and the theory of optical fibres. This equation expresses the gesture of solitons and Madelung fluids in various nonlinear systems. These outcomes are optical, bright, dark, explicit, periodic and combined wave solutions and efficiently demonstrated with the aid of 3D plots. The representation of these solutions is carried out in order to have an idea about the structure of such model and can also be extended to many other complex models of recent era.